Efeitos Ambientais sobre Ganho de Peso no Período do Nascimento ao Desmame em Bovinos da Raça Nelore - De Paz, Claudia Cristina Paro [UNESP]; De Albuquerque, Lúcia Galvão [UNESP]; Fries, Luiz Alberto [UNESP] (FapUNIFESP (SciELO), 1999)
The objective of this work was to study the effects of age of dam (AOD), age of calf (AOC) and Julian date of birth (DOB) on the average daily gain (ADG) from birth to weaning period of Nellore breed animals. The data were analyzed by restricted maximum likelihood, using the animal model. The model included the direct effects of contemporary group (CG), AOD, AOC and DOB, and the direct effects (animal), maternal, permanent environmental and residue. The covariates were defined using segmented polynomials. In view of higher association between the AOC and DOB effects and of the importance of these effects on ADG, estimates with these two effects as a whole were selected. The correlation value between AOC and DOB of -0.60 was a poor indicator of the problems, being the three-dimensional plot very useful. The AGD was significantly influenced by linear and quadratic effects of calf age. The usual way to obtain adjusted weaning weights through AGD can not be adequate for this data set. The Julian birth date is an important effect on ADG and should be included in the model and a segmented polynomial function may be preferable to a discrete parameterization.
Environmental Effects on Weight Gain from the Birth to Weaning Period in Nellore Breed Cattle
Keywords: Age of calf; Beef cattle; Julian date of birth; Multicollinearity; Animalia; Bos taurus